Peningkatan Pembelajaran Pendidikan Agama Islam Melalui Metode Pemberian Tugas Belajar dan Resitasi Pada Siswa Kelas IV SD Alam Qu Ainur Rahmah (Kec. Pasaman Barat Simpang Empat) - Al, Ewiza; Yandri, Rinol Ami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The application of the method of giving learning assignments and recitations at SD Alam Qu Ainur Rahmah. Class VI Action Research has a positive influence, namely it can increase students' learning motivation as shown by the results of interviews with some students, the average student answer stated that students were interested and interested in the methods of giving learning assignments and recitations so that they became motivated to learn. Problem-based learning has a positive impact in improving student learning achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (68.18%), cycle II (77.27%), cycle III (86.36%).